Exploring the fitness hypothesis in ALS: a population-based case-control study of parental cause of death and lifespan. Issue 7 (14th March 2017) - Visser, Anne E; Seelen, Meinie; Hulsbergen, Alexander; de Graaf, Joris; van der Kooi, Anneke J; Raaphorst, Joost; Veldink, Jan H; van den Berg, Leonard H
Abstract : Objective: To investigate the theory of premorbid fitness in amyotrophic lateral sclerosis (ALS), we studied whether a common genetic profile for physical or cardiovascular fitness was manifest in progenitors leading to less cardiovascular death and a longer lifespan in parents of patients with ALS compared with parents of controls. Methods: Patient and disease characteristics, levels of physical activity, parental cause and age of death were obtained using a structured questionnaire from a population-based, case–control study of ALS in the Netherlands. Logistic regression was used for the analyses of parental cause of death and levels of physical activity. Cox proportional hazard models were applied to study the association between parental survival and ALS, or specific patient subgroups. All models were adjusted for age at inclusion, level of education, body mass index, diabetes, hypercholesterolaemia and hypertension. Results: 487 patients and 1092 controls were included. Parents of patients died less frequently from a cardiovascular disease compared with parents of controls (OR=0.78, p=0.009). Their survival, however, was neither significantly longer nor shorter. Neither rates of cardiovascular causes of death, nor survival of parents was related to the extent to which patients were physically active in leisure time (all p > 0.05). Conclusions: Exploring the fitness hypothesis in the pathogenesis of ALS, our findings provide evidence for a shared mechanism underlying a favourable cardiovascular fitness profile and ALS susceptibility.